PENGARUH KUALITAS PELAYANAN, HARGA, DAN CITA RASA PRODUK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABLE INTERVENING PADA 3 RESTO DI KEMUNING - Brutal Wijaya; Moechammad Nasir (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The purpose of this study was to analyze the impact of service quality, price, and product taste on customer loyalty with satisfaction as an intervening variable at 3 Resto in Kemuning. The type of data used in this study is primary data. The population of this study were people in the Central Java region, male and female, who had visited Resto Bali Ndeso, Mbak Ning, and Ndoro Donker. The sampling technique used in this study was non-probabilitay with purposive sampling technique. The number of samples in this study were 104 respondents. The data collection method in this study used an online questionnaire. The analysis method used is descriptive analysis and structural equation model (SEM) analysis with smart partial least square (PLS). The results of this study are service quality, price and taste have a positive and significant effect on customer satisfaction. Customer satisfaction, service quality and taste have a positive and significant influence on customer loyalty. Price has no effect on customer loyalty. Customer satisfaction plays a role in mediating service quality, price, taste to loyalty.